The RNA‐binding protein ILF3 binds to transposable element sequences in SINEUP lncRNAs. Issue 12 (25th October 2019) - Fasolo, Francesca; Patrucco, Laura; Volpe, Massimiliano; Bon, Carlotta; Peano, Clelia; Mignone, Flavio; Carninci, Piero; Persichetti, Francesca; Santoro, Claudio; Zucchelli, Silvia; Sblattero, Daniele; Sanges, Remo; et al.
Abstract : Transposable elements (TEs) compose about half of the mammalian genome and, as embedded sequences, up to 40% of long noncoding RNA (lncRNA) transcripts. Embedded TEs may represent functional domains within lncRNAs, providing a structured RNA platform for protein interaction. Here we show the interactome profile of the mouse inverted short interspersed nuclear element (SINE) of subfamily B2 (invSINEB2) alone and embedded in antisense (AS) ubiquitin C‐terminal hydrolase L1 (Uchl1), an lncRNA that is AS to Uchl1 gene. AS Uchl1 is the representative member of a functional class of AS lncRNAs, named SINEUPs, in which the invSINEB2 acts as effector domain (ED)‐enhancing translation of sense protein‐coding mRNAs. By using RNA‐interacting domainome technology, we identify the IL enhancer‐binding factor 3 (ILF3) as a protein partner of AS Uchl1 RNA. We determine that this interaction is mediated by the RNA‐binding motif 2 of ILF3 and the invSINEB2. Furthermore, we show that ILF3 is able to bind a free right Arthrobacter luteus (Alu) monomer sequence, the embedded TE acting as ED in human SINEUPs. Bioinformatic analysis of Encyclopedia of DNA Elements‐enhanced cross‐linking immunoprecipitation data reveals that ILF3 binds transcribed human SINE sequences at transcriptome‐wide levels. We then demonstrate that the embedded TEs modulate AS Uchl1 RNA nuclear localization to an extent moderately influenced by ILF3. This work unveils the existence of a specific interaction between embedded TEs and an RNA‐binding protein, strengthening the model of TEs as functional modules in lncRNAs.—Fasolo, F., Patrucco, L., Volpe, M., Bon, C., Peano, C., Mignone, F., Carninci, P., Persichetti, F., Santoro, C., Zucchelli, S., Sblattero, D., Sanges, R., Cotella, D., Gustincich, S. The RNA‐binding protein ILF3 binds to transposable element sequences in SINEUP lncRNAs. FASEB J. 33, 13572‐13589 (2019). www.fasebj.org